Globalization and anaphylaxis. Issue 5 (October 2018) - Kase Tanno, Luciana; Ansotegui, Ignacio; Demoly, Pascal
Abstract : Purpose of review: To understand the impact of globalization in the management of anaphylaxis and identify potential strategies to improve patients' care and prevention. Recent findings: Developments in the field of anaphylaxis have been consistently following these globalization trends offering possibilities of collaborations of the allergy community and integrated international initiatives to reach quality care of allergic patients worldwide. Summary: Globalization is the process of interaction and integration between people, companies, and governments worldwide. Developments in the field of anaphylaxis have been following these globalization trends offering possibilities of collaborations and integrated international initiatives to reach quality care of allergic patients worldwide. Complex disorders, such as anaphylaxis, have called for complex integrative strategies, leading to a new acceptance of outside traditions. Allergy is encouraging us to accept holistic and integrative medical practices as viable options. With the dissolution of multinational boundaries and the universal free access to information, the notion of holistic and global-based care is emerging as the new reality of the medicine. We strongly believe that the integrated action plan to the management and prevention of anaphylaxis, just possible through the globalization, is a key health, political and economical move that advocates for the best practice of allergology.